The Influence of Promotion, Price, and Online Shopping Behavior on Purchase Decision on the Shopee Platform: A Case Study of Active Students at Muhammadiyah University Pontianak - Reysha Amelia; Neni Triana M (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the relationship between promotion, price, and online shopping behavior on purchase decisions on the Shopee platform, with a case study involving active students at Universitas Muhammadiyah Pontianak. The research employs a quantitative method with an associative approach. Primary data were collected through questionnaires distributed to 100 respondents, selected using the Slovin formula from a total population of 4,346 students with a margin of error of 10%. The data were analyzed using multiple linear regression. Individually (t-test), the results show that promotion, price, and online shopping behavior have a positive and significant effect on purchase decisions. Simultaneously (F-test), these three variables also significantly influence purchase decisions, with a coefficient of determination (R²) value of 0.479. This means that 47.9% of the variation in purchase decisions can be explained by promotion, price, and online shopping behavior, while the remaining 52.1% is influenced by other factors outside the scope of this study. These findings highlight the importance for e-commerce platforms to continuously enhance promotional strategies, maintain competitive pricing, and provide an optimal user experience to support consumer purchasing decisions. Based on the results, it is recommended that future research consider additional variables such as customer reviews and the quality of delivery services, as these factors are believed to also influence consumer trust and final decision-making in online transactions.